Urban-Rural Disparities in the Continuation of Education after Marriage among Bangladeshi Women - Rahman, Md Mahfuzar; Mondal, Md Nazrul Islam; Islam, Md Rafiqul; Goni, Md Abdul; Haque, Moynul; Parvin, Shela (Thai Social Science Journal, 2026)
Background: Despite significant progress in female education in Bangladesh, many young women discontinue their studies after marriage, with notable disparities observed between urban and rural areas. This study examines the factors associated with the continuation of education after marriage among young Bangladeshi women, with a focus on urban-rural differences. Methods: Data were extracted from the Bangladesh Demographic and Health Survey (BDHS) 2022, which used a two-stage stratified sampling design to ensure national representation across urban and rural areas and all eight administrative divisions of Bangladesh. Multilevel mixed-effects logistic regression model was used to identify the factors associated with the continuation of education after marriage among young women in urban and rural settings. Results: The results revealed that only 19.16% of Bangladeshi women continue their education after marriage, with a higher rate in urban areas (25.51%) than in rural areas (16.80%). Key factors associated with continued education include age at first marriage, household income, and region. Women who married at or after age 18 had significantly higher odds of pursuing education post-marriage. Wealthier women, particularly those from the richest households, were 4 to 5 times more likely to continue education than the poorest. In rural areas, media access and improved household conditions also supported educational continuation. Marked regional disparities were found, especially in Rangpur, Barishal, and Rajshahi. The decline in intraclass correlation from about 17% to 8% in the final models indicates that much of the variation was explained by individual, household, and community-level factors. Conclusions: A small proportion of women in Bangladesh continue their education after marriage, highlighting a critical area of concern. Several key factors- such as socioeconomic status, age at marriage, household conditions, and geographical location- were found to significantly influence the likelihood of postnuptial educational continuation. These findings underscore the need for targeted policy interventions that address early marriage, poverty, and regional disparities. By tackling these issues, policymakers can better support married women in pursuing education, thereby promoting gender equality and contributing to broader socio-economic development in Bangladesh.